Antiarthritic effect of chitosan nanoparticle loaded with embelin against adjuvant‐induced arthritis in Wistar rats. Issue 5 (11th February 2020) - Cui, Peng; Qu, Feng; Sreeharsha, Nagaraja; Sharma, Sanjay; Mishra, Anurag; Gubbiyappa, Shiva K.
Abstract: Background: Rheumatoid arthritis (RA) is associated with joint damage. Effectiveness of embelin has been established in a wide variety of inflammatory disorders, but its utility as a therapeutic agent is limited by its poor absorption, rapid metabolism, and fast systemic elimination. To apprehend these limitations, we propose to use highly bioavailable embelin‐loaded chitosan nanoparticles (CS‐embelin NPs) for the treatment of RA. Methods: The rats were made arthritic using a subcutaneous injection with 0.1 ml complete Freund's adjuvant (CFA) into the footpad of the left hind paw. CS‐embelin NPs (25 and 50 mg/kg) was administered from day 15 to day 28 after adjuvant injection. After the experimental period, the animals were sacrificed and various biochemical markers were assessed. Results: Arthritic score and paw swelling were significantly reduced after treatment with CS‐embelin NPs. Arthritis‐induced rats showed a significant increase in malondialdehyde (MDA) and nitric oxide (NO) with a concomitant reduction of antioxidants in the paw tissue. CS‐embelin NPs (25 and 50 mg/kg) reduced MDA and NO levels and restored antioxidant levels to normalcy by mitigating oxidative stress. The arthritic rats exhibited elevated tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6) and interleukin‐1beta (IL‐1β) serum concentrations, upregulated TNF‐ α and IL–6 protein levels and upregulated nuclear factor‐kB (NF‐kB) mRNA expression in paw tissues. Treatment with CS‐embelin NPs (25 and 50 mg/kg) significantly reduced serum levels and down‐regulated inflammatory markers to normalcy, dose‐dependently. Conclusion: The results suggest that CS‐embelin NPs displayed a protective effect against adjuvant‐induced arthritis in rats mediated through antioxidant and anti‐inflammatory effects.